Learning Discipline and Teacher Performance on Critical Thinking Skills of Students in the Merdeka Belajar Era - Sahade; Imran, Ahmad Fadhil; Sumarwadji, Hafid (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Most teachers find it difficult to stimulate students' critical thinking, especially since the independent learning curriculum was implemented. In fact, the implementation of the curriculum at the same time supports teachers and students to adapt quickly in order to realize the learning process of high order thinking skills. This study was conducted with the aim of analyzing the extent to which learning discipline and teacher performance affect students' critical thinking skills in Vocational High Schools. This type of research is causal relationship research with a quantitative approach. The population in this study were all X AKL class students, totalling 140 students. The sample in this study was 56 students. The data collection techniques used were questionnaires and tests, and then the data were analyzed using descriptive percentages, instrument tests, classical assumption tests, and hypothesis testing. The findings of this study indicate that learning discipline partially has no effect on critical thinking skills, and teacher performance partially affects critical thinking skills. However, simultaneously, learning discipline and teacher performance do not affect students' critical thinking skills in accounting subjects in the era of independent learning.